1998
DOI: 10.1055/s-2006-957506
|View full text |Cite
|
Sign up to set email alerts
|

Flavan-3-ols Isolated from Some Medicinal Plants Inhibiting COX-1 and COX-2 Catalysed Prostaglandin Biosynthesis

Abstract: Extracts from the four plant species Atuna racemosa Raf. ssp. racemosa, Syzygium corynocarpum (A. Gray) C. Muell., Syzygium malaccense (L.) Merr. & Perry and Vantanea peruviana Macbr., traditionally used for inflammatory conditions, were fractionated using a cyclooxygenase-1 catalysed prostaglandin biosynthesis in vitro assay. The flavan-3-ol derivatives (+)-catechin, (+)-gallocatechin, 4'-O-Me-ent-gallocatechin, ouratea-catechin and ouratea-proanthocynidin A were isolated as active principles. The IC50 values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 10 publications
1
42
1
6
Order By: Relevance
“…& Perry), conhecida popularmente no Brasil como jambo vermelho, jambo roxo e jambo encarnado, faz parte das plantas medicinais do Estado de Alagoas, sendo as folhas e os frutos usados como adstringentes e estimulantes do apetite, como diuréticos e no combate a anemias, principalmente pelas populações de baixo poder aquisitivo (Campelo, 1988). Em várias partes do mundo, E. malaccense, é empregada, na medicina popular, no tratamento de processos infl amatórios, febre, coceira, diabetes, catarro no pulmão, tosse, dores de cabeça, disenteria e como diurético (Dunstan et al 1997;Noreen et al 1998). Estudos farmacológicos demonstraram a atividade antiviral seletiva do extrato aquoso da casca do caule frente aos vírus da Herpes Simplex-1 (HSV-1) e 2 (HSV-2), da estomatite vesicular e HIV-1 (Locher et al, 1995;1996), enquanto, o extrato aquoso das folhas revelou forte inibição das bactérias Staphylococcus aureus e do Streptococcus pyogenes (Locher et al, 1995) tendo sido isolado o ácido elágico, o 3-O-metilelágico e o 3,3'-O-dimetilelágico.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…& Perry), conhecida popularmente no Brasil como jambo vermelho, jambo roxo e jambo encarnado, faz parte das plantas medicinais do Estado de Alagoas, sendo as folhas e os frutos usados como adstringentes e estimulantes do apetite, como diuréticos e no combate a anemias, principalmente pelas populações de baixo poder aquisitivo (Campelo, 1988). Em várias partes do mundo, E. malaccense, é empregada, na medicina popular, no tratamento de processos infl amatórios, febre, coceira, diabetes, catarro no pulmão, tosse, dores de cabeça, disenteria e como diurético (Dunstan et al 1997;Noreen et al 1998). Estudos farmacológicos demonstraram a atividade antiviral seletiva do extrato aquoso da casca do caule frente aos vírus da Herpes Simplex-1 (HSV-1) e 2 (HSV-2), da estomatite vesicular e HIV-1 (Locher et al, 1995;1996), enquanto, o extrato aquoso das folhas revelou forte inibição das bactérias Staphylococcus aureus e do Streptococcus pyogenes (Locher et al, 1995) tendo sido isolado o ácido elágico, o 3-O-metilelágico e o 3,3'-O-dimetilelágico.…”
Section: Introductionunclassified
“…Estudos químicos efetuados com as folhas de E. malaccensis levaram ao isolamento de quatro fl avonóides: catequina, mearnsitrina, miricitrina e quercitrina (Noreen et al, 1998); dos frutos foram obtidos compostos voláteis (Pino et al, 2004). A partir das fl ores foi isolada a antocianina, 3,5-diglicosílmalvidina (Lowry, 1976a), enquanto do caule foram isolados os ácidos elágico, 3-Ometilelágico e 3,3'-O-dimetilelágico (Lowry, 1968).…”
Section: Introductionunclassified
“…PAs and their monomeric building blocks catechin and epicatechin are antioxidants with beneficial effects on human health, including cardioprotective (2), anticancer (3), and anti-inflammatory activities (4). PAs in forage plants bind to proteins and slow their fermentation in the rumen, reducing microbial production of methane and thereby protecting the animal from potentially lethal pasture bloat (1).…”
mentioning
confidence: 99%
“…We found that Bucida extract contains gallic acid, catechins, aesculetin, rutin and quercetin. The anti-inflammatory effect may be due to synergistic effect rather than a single constituent Groups Welton et al (1986) demonstrated that quercetin and kaempferol inhibited cyclooxygenase-2 in rat peritoneal macrophages while catechin weakly inhibits cyclooxygenase-2 but a very high concentration (100 μM) (Noreen et al, 1998). Flavonols such as kaemperol, quercetin, morin and myricetin were found to better lipoxygenase inhibitors than flavones.…”
Section: Bucida Bucerasmentioning
confidence: 99%